Bodies and borders in post-imperial Japan: a study of the coloniality of biometric power - Nishiyama, Hidefumi (Cultural studies (London, England), 2022)
In this article, I conduct a study of what may be called the coloniality of biometric power. In recent years, scholars in social sciences and humanities have shown the continuities of colonialism and racism in the politics of biometric identification. Not only are the origins of biometrics closely related to colonial governance and scientific racism, but contemporary biometric technologies also continue to carry on colonial and racial dimensions in their infrastructures and operations. Inspired by Quijano's notion of 'coloniality of power' and departing from existing social and cultural studies of biometrics, the article explores how biometrics is used for the racial classification of people, the (re)production of colonial structures and subject-object relations during and after colonialism. The article focuses on the case of fingerprinting border controls and surveillance in post-imperial Japan. This particular case geographically expands the literature on the relationship between biometrics and colonialism, which has been largely centred upon European and North American contexts. It also helps to understand how one mode of racialization through biometrics is replaced by another, which empowers a new form of racial governance. Drawing on my analysis of the postwar Japanese fingerprinting system, I suggest that it is important to register different forms of racialization through biometrics as there are different forms of racialized control in different historical and geographical contexts.